Measurement and Analysis of the Distribution of Pb-214 Lead Isotope in Baghdad Soil using Remote Sensing Techniques - Hammood, Hadeel Kh.; Al Ramahi, Fouad K. Mashee; Hussain, Hayder S. (Iraqi Journal of Science, 2022)
The present research aims to measure concentration of lead Pb214 in soil using remote sensing and GIS, associated radiological hazards in Baghdad, Iraq. Concentration of specific radioactivity of radioactive elements was measured and analyzed naturally and artificially in 48 soil samples for separate sites from Baghdad, Iraq using crystalline spectroscopy to detect germanium. The average radioactivity concentrations of lead were found, as it was found to have varying values ​​from one site to another, as most of them exceeded the international permissible limit, as the highest concentration was recorded at 180 Bq in the sample H28 in Waziriyah district. Battery Lab (1), and the lowest concentration value is 40Bq in (H4, H15, H45) which represents (Dora Expressway, Mansour Street, Fuel Express, and Mahmoudiya Road 2). Remote sensing data techniques, and Global Positioning System (GPS) have been used to analyze the effect of the isotopic distribution of heavy bullets for the city of Baghdad. Using Geographic Information Systems (GIS), concentrations were measured and observed. Results of interpolation maps showed isotope of lead is concentrated in the center and west of Baghdad, and then graded with fewer values in other sites.